PRIVACY AND CONTROL IN MARK ZUCKERBERG’S DISCOURSE ON FACBEOOK - Zimmer, Michael; Hoffmann, Anna Lauren (AoIR Selected Papers of Internet Research, 2014)
The dominance of online social networking sites, such as Facebook, in much of contemporary life necessarily sparks various questions and concerns in terms of information privacy (boyd & Ellison, 2008; Gross & Acquisti, 2005; Mayer-Schšnberger, 2011; Solove, 2007), online identity and representation (Ellison, Steinfield, & Lampe, 2006; Marwick, 2013), and, broadly, the complexities of social life online (Baym, 2013; boyd, 2014; Dijck, 2013). An important step towards addressing these concerns is to gain a better understanding of how Facebook – the world’s largest social networking site – approaches these debates, how it frames issues of privacy and user rights within its own discourse, and how this framing might be reflected in the design of the platform and the affordances it provides (see, for example, Cheney, Christensen, Conrad, & Lair, 2004). Since the messages propagated by a technology’s purveyors can play a particularly influential role in the development of our knowledge and understanding of that technology (Pfaffenberger, 1992), this paper will approach these questions through the lens of Facebook’s founder and CEO Mark Zuckerberg’s own language. Making use of “The Zuckerberg Files” (Zimmer, 2013) – a digital archive of all public utterances by Facebook’s founder and CEO totaling over 100,000 words – this paper reports the results of a discourse analysis of Zuckerberg’s public language as it relates to related concepts of information privacy and control—as well as attendant concepts of sharing, openness, and the ownership of data.